Women's Leadership Communication in Project-Based Creative Organizations - Firsty Aisyah Izzati; Bambang Dwi Prasetyo; Fitri Hariana Oktaviani (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Research on women's leadership has predominantly focused on gender stereotypes, structural barriers, and leadership challenges, while limited attention has been given to how women leaders use communication to manage organizational relationships in project-based work environments. This study examines how women leaders practice communication in managing organizational relationships within Event Organizer and Wedding Organizer organizations operating in the creative sector in Samarinda, Indonesia. Using a qualitative approach informed by a critical paradigm, data were collected through semi-structured in-depth interviews with eleven women leaders and analyzed using Critical Thematic Analysis (CTA). The findings reveal four interconnected communication practices: building and maintaining relational connections, adapting communication across organizational relationships, managing emotional dynamics in project work, and maintaining coordination through flexible communication. These practices enable women leaders to develop trust, negotiate stakeholder expectations, sustain collaboration, and coordinate project activities across dynamic organizational environments. The study contributes to organizational communication scholarship by demonstrating that leadership communication functions not only as a mechanism for coordination but also as a relational process for sustaining organizational relationships across temporary and continuously changing stakeholder configurations. The findings further contribute to women's leadership scholarship by highlighting how gendered expectations are communicatively negotiated through everyday organizational interactions within project-based creative organizations.